If tan
![\alpha \alpha](https://tex.z-dn.net/?f=+%5Calpha+)
= 2xy/x² - y² prove that : sino = 2xy/x² + y²
Answers
Answered by
2
Given that :
1) 2 cos θ - sin θ = x
2) cos θ - 3 sin θ = y
To Prove :
2x² + y² - 2xy = 5
Proof :
2 x² = 2 ( 2cos θ - sin θ )² = 2 + 6 cos² θ - 8 sin θ. cos θ - (i)
y² = ( cos θ - 3 sin θ )² = 1 + sin² θ - 6 sin θ cos θ - (ii)
2 xy = 2 × (2cos θ - sin θ) (cos θ - 3 sin θ) = 4 + 2 sin² θ - 14 sin θ . cos θ - (iii)
Now adding (i) , (ii) and (iii) we get :
2x² + y² - 2xy = [2 + 6 cos² θ - 8 sin θ. cos θ] + [1 + sin² θ - 6 sin θ cos θ] - [4 + 2 sin² θ - 14 sin θ . cos θ]
⇒ 2x² + y² - 2xy = 6 cos² θ + 6 sin² θ - 1 = 6 (cos² θ + sin² θ) - 1 = 6 (1) - 1 = 5
Similar questions